Management of Powdery Mildew Disease of Vegetable Crops by Organic Materials - Shailbala; Yashaswini, Ch.; Kumar, Amarendra (International Journal of Bio-resource and Stress Management, 2023)
Major vegetable crops are attacked by large number of pathogens cause various diseases. Among the various diseases, powdery mildew disease is one of the major problems in the vegetable growing hilly areas of Uttarakhand which cause economic losses. So various locally available materials i.e. soapnut, pyrite, cow dung, cow urine, mustard oil etc either alone or in combinations was used to manage the powdery mildew disease. Results revealed that soapnut performed significantly superior over other treatments in controlling the powdery mildew disease followed by treatment pyrite. Soapnut recorded only 14.99% disease severity in case of pea cultivar Arkel while 30.83% disease severity was observed in case of pea cultivar VL-7. Control plots of pea cultivar VL-7 and Arkel recorded maximum disease severity i.e. 95.83% and 84.16% respectively. Green pod yield was significantly maximum in treatment soapnut (90.84 q ha-1 in pea cultivar Arkel and 50.19 q ha-1 in pea cultivar VL-7) showing 45.65% and 48.15% increase in yield over control in pea cultivar Arkel and VL-7 respectively followed by pyrite treatment. The similar kinds of results were also recorded against powdery mildew of okra. Outcome of the present investigation has clearly highlighted soapnut as a promising potential against powdery mildew disease of pea and okra. It reduced disease significantly as well as stress of pathogen on crop. In organic state, use of soapnut for disease management can be among the most prefer and accessible plant disease management technology especially for poor.